Elastin-derived peptides enhance melanoma growth in vivo by upregulating the activation of Mcol-A (MMP-1) collagenase - Devy, J (Nature Publishing Group, 2010)
BACKGROUND: Elastin peptides possess several biological activities and in vitro data suggest they could be involved in the early phase of melanoma growth. METHODS: Using diverse in vitro and in vivo techniques (cell proliferation, invasion and migration assays, zymography, western blots, collagen degradation assay, reverse transcription PCR, melanoma allographs and immunohistochemistry), we analysed the effect of elastin-derived peptides (EDPs) on B16F1 melanoma growth and invasion, as well as on the proteolytic systems involved. RESULTS: We found that EDPs dramatically promote in vivo tumour development of B16F1 melanoma, as well as their in vitro migration and invasion. The inhibition of serine proteases and matrix metalloproteinases (MMPs) activities, by aprotinin and galardin, respectively, demonstrated that these enzymes were involved in these processes. However, we found that EDPs did not increase urokinase-type plasminogen activator, tissue-type plasminogen activator or MMP-2 expression and/or activation, neither in vitro nor in vivo. Nevertheless, we observed a strong increase of pro-MMP-9 secretion in EDPs-treated tumours and, more importantly, an increase in the expression and activation of the murine counterpart of MMP-1, named murine collagenase-A (Mcol-A). Moreover, we show that plasminogen system inhibition decreases collagen degradation by this enzyme. Finally, the use of a specific blocking antibody against Mcol-A abolished EDP-induced B16F1 invasion in vitro, showing that this MMP was directly involved in this process. CONCLUSION: Our data show that in vivo, EDPs are involved in melanoma growth and invasion and reinforced the concept of elastin fragmentation as a predictive factor.